Respuesta :

Answer:

The next Step is

The Option is A

( 3x - 1 ) = ± 5

Step-by-step explanation:

Given:

[tex]4(3x-1)^{2} - 17 = 83\\[/tex]

Solution:

Always while square rooting we get two values because square of negative number is also positive number.

Step wise:

[tex]4(3x-1)^{2} - 17 = 83\\\\\\4(3x-1)^{2} = 100\\\\(3x-1)^{2}= 25\\\\\textrm{taking square rooting on both the side we get}\\\\(3x-1) =\pm\sqrt{25}\\\\\\(3x-1)=\pm5\\ \textrm{Which is the required step}\\\\3x=1 \pm5\\3x=6\ or\ 3x =-4\\\\x =2\ or\ x=\frac{-4}{3}[/tex]